UPAYA KYAI DALAM PEMBINAAN AKHLAK UNTUK MENINGKATKAN AKHLAK SANTRI PONDOK PESANTREN - Minanurrohman (UNISAN JURNAL, 2024)
The point of this exploration is to depict the Kyai's endeavors in creating ethics to work on the ethics of understudies at the Tahfizh Al-Qur'an Islamic Life experience School Lil-Muqorrobien Al-Islami Kampung Gabung Makmur Kerinci Kanan Siak. Information assortment techniques were done utilizing perception, meetings and documentation strategies. In the examination, information decrease steps, information show and end drawing are done. In the mean time, to examine it utilizing inductive reasoning. In view of the information got, the consequences of examination on the Execution of Direction Guiding in the Ethical Advancement of Santri at the Tahfizh Al-Qur'an Islamic Life experience School Lil-Muqorrobien Al-Islami Kampung Gabung Makmur Kerinci Kanan Siak show very well and the degree of progress is critical, noticeable from the training members generally partake in advising and moral preparation that utilizes techniques for figuring out, exhortation, inspiration, proposal and adjustment. With the goal that you can gradually change the attributes and propensities for understudies to improve things. There are a few things that impact an understudy's ethical condition, in particular the social climate, specifically their social companions. They will generally copy and follow the atrocities of their loved ones climate, implying that guardians, since they are occupied, give little consideration to the ethics of their understudies.